Diversidad de familias: conformación, revolución socioeconómica y protección jurídico estatal (Tema Central) - Tapia Paredes, José Ernesto (2019)
This work focuses on the diversity of families that can start from physical attraction, or from necessity, or from affection, defying even the reductionist and isolating parameters of the monogamy and the monolove. The content of the article without the intention of deplete the great diversity of families that can be formed, presents several family structures from an approximation of the circumstances of particular origin of each one and includes those families whose consolidation could well move towards elements of broad social integration. Subsequently, the document refers to several circumstances of repression in which affection and femininity have been historical victims and whose effects are not only observed in the field intrafamily if not social. Likewise, the text is concerned with indicating why the conservative interest in maintaining the dominant reductionist monogamous family structure as the only protectable model it is advantageous and convenient for the private production system, contemplating the possibility of revolutionizing the economy at different levels based on the notion of family. Finally, this work makes a quick reference regarding the scope of the legal obligation that the Ecuadorian State has regarding guaranteeing the achievement of the purposes of the diversity of families that may be constituted.